The Relationship Between Sleep Quality with Cognitive Emotion Regulation Strategies and Brain-Behavioral Systems in Pregnant Women - Jahangir Karami; Khodamorad Momeni; Faride Alimoradi (Hamadan University of Medical Sciences, 2018)
Introduction: Reduction of the quality of sleep is one of the most common complaints of women during pregnancy that leads to negative consequences on the mental health of pregnant women. Some factors that associate with quality of sleep are how to use cognitive emotion regulation strategies and brain-behavioral systems. This investigation aims to study the relationship between sleep quality with cognitive emotion regulation strategies and brain-behavioral systems in pregnant women. Methods: This study was conducted in the first half of 2016 on 302 pregnant women who referred to health centers in Kermanshah city and were chosen using cluster sampling method. Subjects completed the Pittsburgh sleep quality questionnaire, Garnefski cognitive emotion regulation strategies questionnaire and Carver and White BIS/BAS questionnaire with a self- assessment method. Data was analyzed using descriptive statistical, Pearson's correlation and regression and statistical and SPSS22. The significant level considered as: (P< 0/05). Results: There was significant relationship between sleep quality with emotion regulation strategies and behavioral inhibition system; the use of negative and maladaptive cognitive emotion regulation strategies and high activity in the behavioral inhibition, decrease the quality of sleep in pregnant women. Conclusion: Using some of the negative and maladaptive cognitive emotion regulation strategies such as rumination and disaster concept, and high activity in behavioral inhibition system can decrease sleep quality in pregnant women.